Experimental investigation on evolution route of pressure drop oscillations under rolling motion based on maximal Lyapunov exponent. (November 2021) - Lin, Yuqi; Gao, Puzhen; Chen, Chong; Tian, Chunping; Chen, Xianbing; Hu, Xiangjie
Highlights: Natural circulation PDO in rolling motion is established in experiment research. Maximal Lyapunov exponent is calculated to analysis chaos characteristics of PDO. Spectrum analysis method is used to reveal the effect of rolling motion on PDO. Frequency-locking oscillation is discovered in composite oscillation of PDO. Resonance oscillation occurs in co-frequency oscillation of PDO. Abstract: A series of experimental study on natural circulation pressure drop oscillations (PDO) under rolling motion are carried out. PDO under rolling motion is a chaotic motion, the thermal–hydraulic mechanism and evolution route are analyzed by maximal Lyapunov exponent and spectrum analysis. When rolling motion has different periods with PDO, composite oscillations are formed. The evolution route can be divided into 3 parts: thermal–hydraulic stable region, frequency-locking oscillation region and rolling effect weakening region. When heat flux is low, PDO is forced to have the same frequency as rolling motion. Frequency-locking oscillation has increasing maximal Lyapunov exponents and a broadband spectrum. But while under high heat flux, rolling effect is weakened. Evolution route of co-frequency oscillations has 3 parts: thermal–hydraulic stable region, bimodal oscillation region and resonance oscillation region. Bimodal oscillation region shows strong chaotic characteristic and cannot form regular waveforms. Rolling motion reduces chaos characteristic when resonance oscillation occurs.